2006
DOI: 10.1002/adma.200502568
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Zirconia–Titania Composite Membranes Derived from Diethanolamine‐Modified Precursors

Abstract: Inorganic microporous materials show great potential for applications in industrial catalysis, separation technology, membranes, sensors, and optical devices. The most common amorphous, microporous inorganic material is silica. Due to its small pores and straightforward synthesis, amorphous silica has been considered as a promising material for membrane applications. However, its moderate hydrothermal stability limits its extended application in harsh environments.[1] Of particular interest as alternative mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…This temperature is considerably higher than that of the crystallization of gamma phase from colloidal boehmite particles [38]. Spijksma et al [44] also reported crystallization at around 750°C in the microporous titania-zirconia composite membranes derived from diethanolamine modified precursors which was considerably higher than *400°C for pure titania and zirconia.…”
Section: Polymeric Solsmentioning
confidence: 99%
“…This temperature is considerably higher than that of the crystallization of gamma phase from colloidal boehmite particles [38]. Spijksma et al [44] also reported crystallization at around 750°C in the microporous titania-zirconia composite membranes derived from diethanolamine modified precursors which was considerably higher than *400°C for pure titania and zirconia.…”
Section: Polymeric Solsmentioning
confidence: 99%
“…Inorganic membranes that can separate hydrogen from CO 2 -containing gas streams with subsequent CO 2 sequestration, offer great potential for integration in pre-combustion CO 2 capture technologies and, hence, being a rather hot topic in the present membrane research field. Several inorganic materials have been proposed to be used as gas separation membranes for such purpose, including zeolites [6][7][8][9], carbon [10][11][12][13], silica and metal oxides [35,36]. Among these, silica-based microporous membranes with the pore size tailored to the gas molecular range is one of the most promising materials since Uhlhorn et al [37] firstly found their molecular sieving performances in 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Different research groups have undertaken numerous attempts to improve the hydrothermal stability of sol-gel derived microporous silica membranes, including (1) modification of the amorphous silica matrix by doping with metal or transition-metal ions (e.g., Ni, Co, Mg, Al, Zr, Ti, Fe, Nb, and others); [4] (2) dispersion of methyl (ÀCH 3 ) functional groups into the silica matrix, so as to make its structure more hydrophobic; [9,10] and (3) use of alternatives to tetraethyl orthosilicate (TEOS) as the source for the alkoxide, such as transition-metal alkoxides or bridged bis-silyl precursors. [11][12][13][14] None of these attempts have succeeded in developing a high-enough membrane performance combined with a sufficient long-term hydrothermal stability to the degree required for application to industrially relevant gas streams and temperatures.Herein, we report on sol-gel derived microporous hybrid inorganic-organic membranes for enhanced CO 2 separation. These are prepared by co-hydrolysis and condensation of the ethylene-bridged bis-silyl precursor 1,2-bis(triethoxysilyl)-ethane (BTESE) and niobium penta(n)butoxide, and subsequent coating of the polymeric sol on an alumina-based multilayer support.…”
mentioning
confidence: 98%